(untitled) (Damu Journal of Sport Sciences, 2025)
Through the progress achieved in learning defensive handball movements and to ensure obtaining the best level and approaching the ideal form of performance and in order to reach the desired goal, it has become our duty to choose appropriate educational programs using hologram technology and effective in order to teach female students and develop them for the better. The research aims to identify the effect of an educational curriculum according to Hologram technology in learning some defensive handball movements for female students. The research hypothesis was that there were statistically significant differences between the pre- and post-tests of the experimental and control groups in defensive handball movements for female students in favor of the experimental group. The researcher selected the research community intentionally, which are female students of Yarmouk School / Al-Rusafa II / Baghdad for the fifth grade of middle school for the academic year 2023-2024. By drawing lots, the choice fell on Section (A), numbering (34), and they were divided into two sections randomly by drawing lots into two groups. The researcher reached the following conclusions: The use of hologram technology in the educational curriculum showed a noticeable improvement in defensive handball movements and overall performance compared to traditional training. Technology Holograms enhance motor learning and contribute to improving students' self-confidence by providing an interactive and immersive training environment.